The Western Diet and Atopic Dermatitis: The Potential Role of Nutrients, Contaminants, and Additives in Dysbiosis and Epithelial Barrier Dysfunction - Chiara Maria Teresa Boggio; Federica Veronese; Marta Armari; Elisa Zavattaro; Elia Esposto; Paola Savoia; Barbara Azzimonti (Antioxidants)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder influenced by both genetic and environmental factors, collectively termed the exposome. Among these determinants, diet emerges as a pivotal component, with diverse nutrients, contaminants, and additives shaping immune responses, microbiota composition, and systemic inflammatory status. This literature review aimed to elucidate the interplay between dietary factors and skin dysbiosis in AD, providing insights into how these interactions may impact disease susceptibility and progression. A comprehensive search of PubMed and Scopus was conducted using relevant keywords and medical subject headings (MeSH). Studies published in English within the past 25 years were included, encompassing in vitro, in vivo, and ex vivo research, as well as reviews. Priority was given to frequently cited articles, reflecting significant contributions to current understanding. Findings suggest that dietary habits influence AD by modulating both gut and skin microbiota, immune pathways, and inflammatory processes. These insights underscore the importance of considering diet within a broader exposome framework, paving the way for targeted interventions to improve AD management. Further research is needed to clarify the mechanisms and optimize nutritional strategies, potentially informing preventive and therapeutic approaches for AD.